2020
DOI: 10.3390/vetsci8010005
|View full text |Cite
|
Sign up to set email alerts
|

Small Ruminant Production in Tanzania, Uganda, and Ethiopia: A Systematic Review of Constraints and Potential Solutions

Abstract: Sheep and goats are an important commodity for smallholder farmers across East Africa, but severe limitations remain in small ruminant production. This review aimed to identify specific constraints to small ruminant production and identify practical and sustainable solutions. From 54 eligible articles, most were focused in Ethiopia (n = 44) with only 6 studies performed in Tanzania and 4 in Uganda. The most frequently identified constraint in Ethiopia and Tanzania was disease (n = 28 and n = 3, respectively), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 66 publications
0
13
0
Order By: Relevance
“…Various papers underline how limited access to veterinary services is a major problem for livestock producers in sub-Saharan countries: see the issues of the OIE review dedicated to Veterinary institutions in the developing world: current status and future needs with a special focus on SSA countries in 2004 and the issue Good governance and financing of efficient veterinary services in 2012; as well as the recent review of Abakar et al ( 32 ) on the status of veterinary services in the Sahel over the last 20 years. Other studies focus on a specific country or group of countries such as Kenya and Uganda ( 47 50 ), Tanzania ( 51 ), Central Africa ( 52 ), South Africa ( 53 , 54 ), or Tanzania, Uganda, and Ethiopia ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…Various papers underline how limited access to veterinary services is a major problem for livestock producers in sub-Saharan countries: see the issues of the OIE review dedicated to Veterinary institutions in the developing world: current status and future needs with a special focus on SSA countries in 2004 and the issue Good governance and financing of efficient veterinary services in 2012; as well as the recent review of Abakar et al ( 32 ) on the status of veterinary services in the Sahel over the last 20 years. Other studies focus on a specific country or group of countries such as Kenya and Uganda ( 47 50 ), Tanzania ( 51 ), Central Africa ( 52 ), South Africa ( 53 , 54 ), or Tanzania, Uganda, and Ethiopia ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…Based on genetic relationships between PPR viruses from different geographical regions, Shaila et al ( 2 ) reported that PPRVs have undergone independent evolution which has resulted in four genetic subtypes (PPRV lineages I–IV). PPR is a disease of mainly goats and sheep with high morbidity and mortality that can reach 100 and 90%, respectively ( 3 ) and consequently is a major constraint to small ruminant production ( 4 , 5 ). Evidence of PPRV infection has also been identified in camels ( 6 , 7 ), cattle ( 8 ), buffaloes ( 9 ) and several wildlife species, however their role in PPR viral circulation has not been properly elucidated ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their prominent economic contribution to poor rural communities of developing countries, the production and productivity of small ruminants are affected by different health constraints, among which gastrointestinal nematodiosis is the major one [ 10 , 11 ]. The gastrointestinal tract is the primary predilection site for harboring nematode parasites of small ruminants [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In South Omo zone, one of the leading pastoral areas in Ethiopia, small ruminants have paramount importance for the livelihood of the resident pastoral communities [ 21 ]. However, the production and productivity of small ruminants is limited due to poor genetic potential, different diseases, poor nutrition (in quantity and quality), and poor management and husbandry practices [ 11 ]. Among the diseases, GIN infections are suspected to be the most important causes of wastage and decreased productivity of the South Omo zone’s small ruminants, despite scant information.…”
Section: Introductionmentioning
confidence: 99%